A novel shell-like supramolecular assembly of 4, 4′-bipyridyl derivatives and a twisted cucurbit[14]uril molecule1. Issue 49 (21st June 2015) - Liu, Qing; Li, Qing; Cheng, Xiao-Jie; Xi, Yun-Yun; Xiao, Bo; Xiao, Xin; Tang, Qing; Huang, Ying; Tao, Zhu; Xue, Sai-Feng; Zhu, Qian-Jiang; Zhang, Jian-Xin
<x xml:space="preserve">Abstract</x> This work showed that the bipyridyl core and alkyl chains of 4, 4′-bipyridyl derivatives are located in shell-like cavities of the twisted cucurbit[14]uril molecule and formed novel shell-like 1 : 1 inclusion complexes.